2001
DOI: 10.1016/s0006-8993(01)02685-3
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific transcriptional response to chronic nicotine in rat brain

Abstract: Even though nicotine has been shown to modulate mRNA expression of a variety of genes, a comprehensive high-throughput study of the effects of nicotine on the tissue-specific gene expression profiles has been lacking in the literature. In this study, cDNA microarrays containing 1117 genes and ESTs were used to assess the transcriptional response to chronic nicotine treatment in rat, based on four brain regions, i.e. prefrontal cortex (PFC), nucleus accumbens (NAs), ventral tegmental area (VTA), and amygdala (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 55 publications
3
75
0
Order By: Relevance
“…Microarray production, cDNA probe labeling, and array hybridization A pathway-focused microarray consisting of 638 sequence-verified genes that was designed by our laboratory (called the homeostatic pathway-focused array) was used [52]. This array contains 638 sequence-verified genes selected from rat cDNA clones (Research Genetics, AL) and the 15K NIA mouse cDNA gene set [52] on the basis of our previous studies [28,37]. It was shown that cross-species hybridization (i.e., mouse clones against rat target samples) using a cDNA platform is accurate and specific [59].…”
Section: Total Rna Isolation and Amplificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Microarray production, cDNA probe labeling, and array hybridization A pathway-focused microarray consisting of 638 sequence-verified genes that was designed by our laboratory (called the homeostatic pathway-focused array) was used [52]. This array contains 638 sequence-verified genes selected from rat cDNA clones (Research Genetics, AL) and the 15K NIA mouse cDNA gene set [52] on the basis of our previous studies [28,37]. It was shown that cross-species hybridization (i.e., mouse clones against rat target samples) using a cDNA platform is accurate and specific [59].…”
Section: Total Rna Isolation and Amplificationmentioning
confidence: 99%
“…The slides were printed by the GMS 417 arrayer (Affymetrix, Santa Clara, CA) according to the protocols suggested by the manufacturer. cDNA probe labeling and array hybridization were performed as described previously with slight modifications [28,29].…”
Section: Total Rna Isolation and Amplificationmentioning
confidence: 99%
See 3 more Smart Citations